Mysterious Oropouche virus: Transmission, symptoms, and control - Sejal Porwal; Rishabha Malviya; Sathvik Belagodu Sridhar; Javedh Shareef; Tarun Wadhwa (Infectious Medicine)
The Oropouche virus (OROV) is a new zoonotic arbovirus that mostly affects Brazil and nearby countries. Since its discovery in 1955, it has caused more than 500,000 infections, with symptoms ranging from fever and headache to serious neuroinvasive disorders such as meningitis and encephalitis. The virus spreads through urban and sylvatic cycles via vectors such as Culicoides midges and Culex mosquitos, with humans and some vertebrates serving as amplifying hosts. The manuscript aims to analyze the transmission dynamics, clinical manifestations, diagnostic approaches, and potential preventive strategies for OROV. OROV is becoming an increasing health concern due to its global expansion and potential for serious consequences. Its growing threat, especially in light of the possibility of congenital abnormalities, is highlighted by the first recorded deaths in 2024 and the verification of vertical transmission. Clinical symptoms overlap greatly with other arboviruses, limiting early diagnosis; nonetheless, molecular approaches such as RT-PCR are crucial for identification. The current therapy is restricted to symptom control, highlighting the critical need for effective vaccinations. Live attenuated vaccination candidates and innovative techniques based on reverse genetics systems are both promising discoveries. However, the genetic variety of OROV strains poses obstacles to obtaining broad protection. To combat OROV, improved surveillance, strong public health initiatives, and quick vaccine development are needed. Public education and sustainable vector control are also essential for controlling outbreaks and lessening the virus effects.